Prognostic value of strain by feature-tracking cardiac magnetic resonance in arrhythmogenic right ventricular cardiomyopathy. (13th February 2022) - Bourfiss, M; Prakken, N H J; James, C A; Planken, R N; Boekholdt, S M; Ahmetagic, D; van den Berg, M P; Tichnell, C; Van der Heijden, J F; Loh, P; Murray, B; Tandri, H; et al.
Abstract: Aims: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is characterized by ventricular dysfunction and ventricular arrhythmias (VA). Adequate arrhythmic risk assessment is important to prevent sudden cardiac death. We aimed to study the incremental value of strain by feature-tracking cardiac magnetic resonance imaging (FT-CMR) in predicting sustained VA in ARVC patients. Methods and results: CMR images of 132 ARVC patients (43% male, 40.6 ± 16.0 years) without prior VA were analysed for global and regional right and left ventricular (RV, LV) strain. Primary outcome was sustained VA during follow-up. We performed multivariable regression assessing strain, in combination with (i) RV ejection fraction (EF); (ii) LVEF; and (iii) the ARVC risk calculator. False discovery rate adjusted P -values were given to correct for multiple comparisons and c-statistics were calculated for each model. During 4.3 (2.0–7.9) years of follow-up, 19% of patients experienced sustained VA. Compared to patients without VA, those with VA had significantly reduced RV longitudinal ( P ≤ 0.03) and LV circumferential ( P ≤ 0.04) strain. In addition, patients with VA had significantly reduced biventricular EF ( P ≤ 0.02). After correcting for RVEF, LVEF, and the ARVC risk calculator separately in multivariable analysis, both RV and LV strain lost their significance [hazard ratio 1.03–1.18, P > 0.05]. Likewise, while strain improved the c-statistic in combination with RVEF, LVEF, and the ARVC risk calculator separately, this did not reach statistical significance ( P ≥ 0.18). Conclusion: Both RV longitudinal and LV circumferential strain are reduced in ARVC patients with sustained VA during follow-up. However, strain does not have incremental value over RVEF, LVEF, and the ARVC VA risk calculator. Graphical Abstract: